Correction: Type 2 Diabetes Risk Allele Loci in the Qatari Population. - Sarah L O'Beirne; Jacqueline Salit; Juan L Rodriguez-Flores; Michelle R Staudt; Charbel Abi Khalil; Khalid A Fakhro; Amal Robay; Monica D Ramstetter; Iman K Al-Azwani; Joel A Malek; Mahmoud Zirie; Amin Jayyousi; et al. (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0156834.].